Families and new media : comparative perspectives on digital transformations in law and society - Dethloff, Nina, 1958-; Kaesling, Katharina; Specht-Riemenschneider, Louisa (Juridicum - Schriften zum Medien-, Informations- und Datenrecht,, 2023)
The open access edited volume addresses childrens rights and their ability to act in the digital world. The focus is on the position of children as subjects with their own rights and developing capacities. Their consideration by parents, courts and legislators is critically examined. Aspects of digital parenting, especially educational practices and strategies in the context of social media, are analyzed with regard to the tension between protection and participation of children. The edited volume brings debates on privacy and data protection together with those from tort, family and intellectual property law, while also examining the role of families and children in the regulation of data and digital economies, especially online platforms. Legal reflections from Germany, Israel, Portugal and the United States of America are complemented by perspectives from media studies, political science, educational science and sociology of law. The Editors: Nina Dethloff, Professor of Civil Law, Private International Law, Comparative Law and European Private Law, University of Bonn, Germany Katharina Kaesling, Tenure Track Junior Professor of Civil Law, Intellectual Property, in particular Patent Law, and Legal Issues of AI, University of Dresden (TU), Germany Louisa Specht-Riemenschneider, Professor of Civil Law, Information and Data Law, University of Bonn, Germany.